The learning curve associated with the implantation of the Nanostim leadless pacemaker - Tjong, Fleur V Y; Beurskens, Niek E G; Neuzil, Petr; Defaye, Pascal; Delnoy, Peter-Paul; Ip, John; Guerrero, Juan Jose Garcia; Rashtian, Mayer; Banker, Rajesh; Reddy, Vivek; Exner, Derek; Sperzel, Johannes; et al. (Journal of interventional cardiac electrophysiology, 2018)
PURPOSE: Use of novel medical technologies, such as leadless pacemaker (LP) therapy, may be subjected to a learning curve effect. The objective of the current study was to assess the impact of operators' experience on the occurrence of serious adverse device effects (SADE) and procedural efficiency. METHODS: Patients implanted with a Nanostim LP (Abbott, USA) within two prospective studies (i.e., LEADLESS ll IDE and Leadless Observational Study) were assessed. Patients were categorized into quartiles based on operator experience. Learning curve analysis included the comparison of SADE rates at 30 days post-implant per quartile and between patients in quartile 4 (> 10 implants) and patients in quartiles 1 through 3 (1-10 implants). Procedural efficiency was assessed based on procedure duration and repositioning attempts. RESULTS: Nanostim LP implant was performed in 1439 patients by 171 implanters at 60 centers in 10 countries. A total of 91 (6.4%) patients experienced a SADE in the first 30 days. SADE rates dropped from 7.4 to 4.5% (p = 0.038) after more than 10 implants per operator. Total procedure duration decreased from 30.9 ± 19.1 min in quartile 1 to 21.6 ± 13.2 min (p < 0.001) in quartile 4. The need for multiple repositionings during the LP procedure reduced in quartile 4 (14.8%), compared to quartiles 1 (26.8%; p < 0.001), 2 (26.6%; p < 0.001), and 3 (20.4%; p = 0.03). CONCLUSIONS: Learning curves exist for Nanostim LP implantation. Procedure efficiency improved with increased operator experience, according to a decrease in the incidence of SADE, procedure duration, and repositioning attempts.
Keywords: kardiostimulátor; Arrhythmia; implantované elektrody; Learning Curve; logistické modely; Pacemaker; Humans; Monitoring, Physiologic; Task Performance and Analysis; plnění a analýza úkolů; Multivariate Analysis; Leadless pacing; Equipment Design; Female; Aged; internacionalita; Internationality; Time Factors; Cardiac Pacing, Artificial; Cardiac Electrophysiology; senioři; lidé; srdeční elektrofyziologie; křivka učení; časové faktory; monitorování fyziologických funkcí; Electrodes, Implanted; ženské pohlaví; multivariační analýza; Male; Learning curve; srdeční arytmie; prognóza; design vybavení; Aged, 80 and over; senioři nad 80 let; Arrhythmias, Cardiac; kardiostimulace umělá; mužské pohlaví; prospektivní studie; Pacemaker, Artificial; Logistic Models; Prognosis; Prospective Studies